Urban Parks: from romanticizing to sanitation – from theory to reality - Martins, Larissa Fernanda Vieira (Revista Nacional de Gerenciamento de Cidades, 2022)
Urban parks have always accompanied the history of man. They represent the main areas for leisure, recreation and contact with nature in city environments. Identifying the formation and transition processes of these spaces reveals the influences that determined parks’ profiles as they are today. This article sets out to trace the historical, conceptual and functional evolution of urban parks and identify tendencies in the typologies of new parks. The historical method is employed whereby investigations of processes in the past enable a verification of their influence on present day society. In the past, parks emerged to improve urban populations’ quality of life in the post-industrialization period whereas, nowadays, parks seek to strike a balance between built up areas and natural ones. Against that background parks are a response to the needs and aspirations of the population in each historical period of its living experience. Currently the most frequently proposed park typology is that of ‘linear parks’ associated to water courses. Given the absence of spaces in cities that would enable the maintenance of ecological integrity in valley-bottoms, and the advanced state of degradation of those environments, new parks tend to be designed from a sanitation perspective as their functionalities can foster flood control by means of permeable areas, avoidance of irregular occupation by attributing new land use, and contributions to the quality of life by making leisure and recreation spaces available. This research contributes by systematizing the evolutive process and identifying tendencies in the configuration of new parks to address contemporary needs..